Avenues for the reduction of LDC-debt: An institutional analysis - Günter Franke (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1990)
This paper compares different instruments for a debt relief, given severe debt servicing problems of some sovereign debtors. Criteria for a debt relief are discussed. First, it will be argued that a debt relief cannot be supported by the argument that it benefits both, the debtor and the creditors. Second, debt reliefs have no chance to be realized if they are a "free lunch" to the debtor. Some cost has to be borne by the debtor. Third, if the debtor is actively involved in the debt relief, then the creditors will make sure by appropriate instruments that the debtor cannot raise the wealth transfer ex post to his benefit at the creditors' expense. Fourth, debt reliefs with deterministic claim reductions are inefficient. Contingent claim reductions involve smaller wealth transfers. If these reductions are made dependent on observable commodity prices, then state verification costs can be avoided and the creditors may hedge the price risk.
Keywords: 330